Qur’anic Exegesis as A Social Critique: A Study on the Traditionalist Bisri Musthofa’s Tafsīr al-Ibrīz - Abidin, Ahmad Zainal; Nurain, N.; Aziz, Thoriqul; Noorhidayati, Salamah (Al-Jami'ah: Journal of Islamic Studies, 2024)
This article examines Tafsīr al-Ibrīz, a Javanese exegetical work of the Quran authored by the traditionalist Muslim scholar Kyai Bisri Musthofa (1915–1977). Adopting a dialogical approach to tafsr literature, the study seeks to explore the intersection between the scriptural text and the sociocultural contexts that the exegete engages with. Written during a period marked by the intensification of Islamic reform and modernization, al-Ibrīz offers valuable historical insights into these dynamics, as well as the exegete’s responses and critiques of contemporary socio-religious challenges in Indonesia. Through a critical-dialectical epistemological framework, the article underscores two significant aspects: the intellectual perspective of the author and the socio-cultural milieu in which the book was produced. Furthermore, it contends that Bisri Musthofa epitomizes a defender of Islamic traditionalism, whose religious authority is articulated through classical Islamic scholarship. His book embodies the responses of traditionalist Muslims to the processes of modernization and rationalization in late 20th-century Indonesia, addressing issues spanning economics, theology, and ethics.[Artikel ini mengkaji Tafsir al-Ibrīz, sebuah karya tafsir al-Qur’an Jawa yang ditulis oleh ulama tradisionalis, Kyai Bisri Musthofa (1915–1977). Dengan menggunakan pendekatan dialogis literatur tafsir, penelitian ini berupaya untuk mengeksplorasi persinggungan antara teks kitab suci dan konteks sosial budaya yang dihadapi oleh penafsir. Ditulis selama periode yang ditandai oleh intensifikasi reformasi dan modernisasi Islam, al-Ibrīz menawarkan wawasan sejarah yang berharga serta tanggapan dan kritik penafsir terhadap tantangan sosial-keagamaan kontemporer di Indonesia. Melalui kerangka epistemologis dialektis-kritis, artikel ini menggarisbawahi dua aspek penting: perspektif intelektual penyusun dan lingkungan sosial-budaya tempat buku tersebut disusun. Lebih jauh, penulis berpendapat bahwa Bisri Musthofa merupakan lambang pembela tradisionalisme Islam, yang otoritas keagamaannya diartikulasikan melalui keilmuan Islam klasik. Tafsir al-Ibrīz merangkum respons kaum Muslim tradisionalis terhadap proses modernisasi dan rasionalisasi di Indonesia akhir abad ke-20, dengan membahas isu-isu yang mencakup ekonomi, teologi, dan etika.]